393 Cancer risks among Canadian agricultural workers in a population-based cohort. (11th October 2013) - Kachuri, L K; Harris,; Peters,; Tjepkema,; Demers,
Abstract : Objectives: Agricultural workers may be exposed to several potential carcinogens including pesticides, sensitising agents and solar radiation. Previous studies have shown increased risks of hematopoietic cancers in this population, as well as reduced risks of other types of cancer, possibly due to differences in lifestyle and risk behaviours. This study aimed to estimate cancer risks among agricultural workers in a national population-based cohort. Methods: The 1991 Canadian Census Cohort was created by Statistics Canada through probabilistic linkage between the 1991 Canadian Census (long form) to national cancer registry records from 1969–2003. Occupations were self-reported. Analyses were restricted to persons aged 74 and under who reported working at baseline (1991, total cohort N = 2050300). Follow-up continued until December 31, 2003. Hazard ratios (HR) and corresponding 95% confidence intervals were estimated by Cox proportional hazards modelling for all workers in agricultural occupations (N = 70300; 49000 male), stratified by sex and adjusted for age at cohort entry and province of residence. Results: There were 5437 cancer cases among agricultural workers. Among men, an increased risk of multiple myeloma was observed (HR: 1.38, 1.04–1.83), as well as oral cancer (HR: 1.28, 1.09–1.51), specifically lip cancer (HR: 2.94, 2.26–3.83), but had decreased risks of lung, esophageal, and liver cancers. Female agricultural workers were at increased risk of pancreatic cancer (HR: 1.44, 1.05–1.99), but decreased risk of lung, breast and cervix cancer. Higher risks of rectal cancer were also observed specifically among female farm workers and labourers (HR: 1.44, 1.02–2.04). Conclusions: Exposure to pesticides may have contributed to the increased risks of multiple myeloma in men and pancreatic cancer in women. Increased risks of lip cancer in men could be attributed to sun exposure in agricultural workers while the array of decreased risks suggests reduced smoking and alcohol consumption in agricultural workers compared to the general population.